2010
DOI: 10.1007/s10461-010-9793-x
|View full text |Cite
|
Sign up to set email alerts
|

People with HIV in HAART-Era Russia: Transmission Risk Behavior Prevalence, Antiretroviral Medication-Taking, and Psychosocial Distress

Abstract: Russia has seen one of the world’s fastest-growing HIV epidemics. Transmission risk behavior, HAART-taking, and psychosocial distress of the growing population of Russian people living with HIV (PLH) in the HAART era are understudied. Participants of a systematically-recruited cross-sectional sample of 492 PLH in St. Petersburg completed measures of sexual and drug injection practices, adherence, perceived discrimination, and psychosocial distress. Since learning of their status, 59% of participants had partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
4
26
1
1
Order By: Relevance
“…Differently, our results seem to confirm Sarkar and col. (1995) results, which defend that harmful behaviors among IDUs are not influenced by knowledge on HIV transmission or HIV testing serostatus. Similar to our results, other evidence also shows that among HIV infected individuals who inject drugs about 40% still share needles or do not use condoms (Amirkhanian et al, 2011). Thus, it is a concern to understand the factors related with behavioral change and with safe injecting practices, besides education.…”
Section: Discussionsupporting
confidence: 90%
“…Differently, our results seem to confirm Sarkar and col. (1995) results, which defend that harmful behaviors among IDUs are not influenced by knowledge on HIV transmission or HIV testing serostatus. Similar to our results, other evidence also shows that among HIV infected individuals who inject drugs about 40% still share needles or do not use condoms (Amirkhanian et al, 2011). Thus, it is a concern to understand the factors related with behavioral change and with safe injecting practices, besides education.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that fear of being publically identified as having HIV represents a serious barrier to care in Ida-Virumaa, and these findings coincide with those of other studies that examined fear of being identified as having HIV in other postSoviet countries (Y. Amirkhanian et al, 2011;Y. A. Amirkhanian, Kelly, & McAuliffe, 2003;Balabanova, Coker, Atun, & Drobniewski, 2006;Bobrova et al, 2006;King et al, 2013;Mimiaga et al, 2010;Rhodes et al, 2006;Rhodes et al, 2012;Sarang et al, 2010;Shilovskaya;Zigon, 2011).…”
Section: Fear Of Disclosuresupporting
confidence: 89%
“…2 Russia has one of the most rapidly increasing HIV epidemics. Statistics indicate that the number of new cases of HIV in Russia is increasing by [7][8][9][10][11][12].9% every year, while the number of people tested for HIV is decreasing. [3][4][5] Between 2001 and 2013, the prevalence of HIV has increased from 121 to 432 per 100,000 people.…”
mentioning
confidence: 99%
“…8 Several factors increase the risk of contracting HIV in Russia and Eastern Europe, including low perception of vulnerability, low acceptance of protective measures such as condom use, high rates of injection drug use, stigma associated with HIV, and widespread risky sexual behaviors. [9][10][11][12][13][14] Unlike the United States, where the number of cases attributed to heterosexual contacts has stabilized, 15 this number has continued to increase in Russia. In 2013, unprotected sex was identified as the main HIV transmission factor in 41% of new infections.…”
mentioning
confidence: 99%